Pengaruh Intensitas Bermain Game Online Terhadap Kebiasaan Mengumpat Pada Remaja Di Kelurahan Panggung Kecamatan Tegal Timur Kota Tegal - Susan Dwi Oktafiani; Sarwo Edy; Diryo Suparto (Badan Penerbit STIEPARI Press, 2022)
The intensity of playing online games for adolescents in Sub District of Panggung, Tegal Timur District, Tegal City, has caused them to practice swearing. The purpose of this study was to see the effect of playing online games on the habit of swearing in adolescents in Sub District of Panggung, Tegal Timur District, Tegal City. This research uses quantitative methods. The data technique used was observation, questionnaires and supporting documents. The population of this study were all of the people of Sub District of Panggung, East Tegal District, Tegal City, with a total sample of 100 respondents. Data were analyzed using simple linear regression test. The results showed that there was an effect of online games on the habit of swearing in adolescents in Sub District of Panggung, Tegal Timur District, Tegal City.